2009
DOI: 10.1371/journal.pone.0005045
|View full text |Cite|
|
Sign up to set email alerts
|

High-Fat Diet Induces Apoptosis of Hypothalamic Neurons

Abstract: Consumption of dietary fats is amongst the most important environmental factors leading to obesity. In rodents, the consumption of fat-rich diets blunts leptin and insulin anorexigenic signaling in the hypothalamus by a mechanism dependent on the in situ activation of inflammation. Since inflammatory signal transduction can lead to the activation of apoptotic signaling pathways, we evaluated the effect of high-fat feeding on the induction of apoptosis of hypothalamic cells. Here, we show that consumption of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
295
2
33

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(345 citation statements)
references
References 32 publications
15
295
2
33
Order By: Relevance
“…Thus, it seems that long-term obesity results in a resetting of the hypothalamic adipostat, as proposed previously (1,43). Experimental studies have shown that upon prolonged feeding on an HFD, hypothalamic neurons may undergo severe damage that may result in apoptosis (17,44). Interestingly, at least three distinct studies have identified POMC (proopiomelanocortin) neurons as the main targets of inflammation-associated apoptosis (17,44,45).…”
Section: Chronic Diet-induced Hypothalamic Inflammation Disrupts Neurmentioning
confidence: 62%
See 2 more Smart Citations
“…Thus, it seems that long-term obesity results in a resetting of the hypothalamic adipostat, as proposed previously (1,43). Experimental studies have shown that upon prolonged feeding on an HFD, hypothalamic neurons may undergo severe damage that may result in apoptosis (17,44). Interestingly, at least three distinct studies have identified POMC (proopiomelanocortin) neurons as the main targets of inflammation-associated apoptosis (17,44,45).…”
Section: Chronic Diet-induced Hypothalamic Inflammation Disrupts Neurmentioning
confidence: 62%
“…Experimental studies have shown that upon prolonged feeding on an HFD, hypothalamic neurons may undergo severe damage that may result in apoptosis (17,44). Interestingly, at least three distinct studies have identified POMC (proopiomelanocortin) neurons as the main targets of inflammation-associated apoptosis (17,44,45). Progressive reduction in hypothalamic POMC neuron population results in an imbalance in POMC/NPY (neuropeptide Y) neurons, which may provide a cellular basis for explaining the resetting of the hypothalamic adipostat.…”
Section: Chronic Diet-induced Hypothalamic Inflammation Disrupts Neurmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the orexigenic agouti-related peptide (AgRP)-expressing neuron also resides in the ARC that controls food intake, and ablation of AgRP neuron in adult mice has been shown to result in significantly reduced food intake (Luquet et al 2005). It has also been reported that an HFD induces apoptosis of AgRP neuron (Moraes et al 2009). These results suggest that long-term HFD and exercise training may have broad effects on both orexigenic and anorexigenic neurons in the ARC.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that consumption of a fat-rich diet blunts leptin and insulin orexigenic signaling by a mechanism dependent on in situ activation of inflammation that could induce apoptosis of neurons and a reduction of synaptic inputs in the arcuate nucleus and lateral hypothalamus (31,32). Wang et al showed that apoptotic hepatocytes were significantly greater in livers of rats fed HFD, and these were associated with a higher level of cleaved caspase-3 (33).…”
Section: Discussionmentioning
confidence: 99%